2005
DOI: 10.1001/archotol.131.11.1017
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of Intracranial Abscesses and Their Associated Sinusitis

Abstract: To evaluate the organisms recovered from infected sinuses and associated intracranial abscesses (IAs). Design: Retrospective review of findings from aspirate of pus from 10 infected sinuses and their corresponding IAs. Setting: Academic medical center. Patients: Ten patients diagnosed as having sinusitis (age range, 7-58 years). Main Outcome Measure: Aerobic and anaerobic bacteria findings from infected sinuses and IAs. Results: Polymicrobial flora was found in 9 sinuses and 8 IAs. Anaerobes were isolated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
26
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 16 publications
(25 reference statements)
4
26
1
1
Order By: Relevance
“…Negative culture rates are a measure of prior antibiotic consumption, specimen handling and laboratory standards, and may vary widely from 0% to above 50%. 6,12 In this study, the negative culture rate of 27.9% is comparable to that encountered in similar studies. 2,4,11 Recent publications mention S. milleri as being the most common pathogen in patients with complicated sinusitis.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Negative culture rates are a measure of prior antibiotic consumption, specimen handling and laboratory standards, and may vary widely from 0% to above 50%. 6,12 In this study, the negative culture rate of 27.9% is comparable to that encountered in similar studies. 2,4,11 Recent publications mention S. milleri as being the most common pathogen in patients with complicated sinusitis.…”
Section: Discussionsupporting
confidence: 87%
“…Reports from several smaller studies quote higher isolation rates, ranging from 7.7% to 11.9%. 1,2,4,6,8,12 On the other hand, total absence of S. pneumoniae is also reported. 7 Studies have shown M. catarrhalis to be a frequent isolate in cultures from patients with acute sinusitis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations